PENGEMBANGAN LKS MATERI POKOK ENERGI DALAM SISTEM KEHIDUPAN DI KELAS VII SMP DENGAN PENDEKATAN ILMIAH UNTUK MENGEMBANGKAN KETERAMPILAN PROSES SAINS - Rena Myrna Myrna; Evi Suryawati Suryawati; Suwondo ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aim of this study was to development of worksheets topic energy in live for junior high school grade seven with scientific approach to improve science process skills. This study held on June until December 2014. This study conducted with assessment worksheet paper, respondent paper, and observation scientific process skills paper. The assessment worksheet paper consist of 27 items and is 4 aspects. The aspect are content expert, linguist, presentation expert, and to encourage students to learn and work scientifically. This study was conducted using method of Research and Development of model ADDIE. The result showed of the experts’ assessment who developed products of content experts was very valid (M=3.53), linguist was very valid (M=3.48), presentation experts was very valid (M=3.51), and work scientifically was very valid (M=3.41). In addition for the scientific process skills students have achieved good category. That result indicated the product that has been developed worthy used in science teaching in schools and can improved science process skills. Key words:Scientific Approach; Science Process Skills; Development of Worksheet